Safety and Feasibility of Video-Assisted Thoracoscopic Day Surgery and Inpatient Surgery in Patients With Non-small Cell Lung Cancer: A Single-Center Retrospective Cohort Study - Dong, Yingxian; Shen, Cheng; Wang, Yan; Zhou, Kun; Li, Jue; Chang, Shuai; Ma, Hongsheng; Che, Guowei (Frontiers in Surgery, 2021)
Abstract Background and objective: This study was undertaken to evaluate how safe and viable the use of video-assisted thoracoscopic day surgery (VATDS) is for individuals diagnosed with early-stage nonsmall cell lung cancer (NSCLC). Methods: Data obtained from selected NSCLC patients who underwent video-assisted thoracoscopic surgery (VATS) in the same medical group were analyzed, and a single-center, propensity-matched cohort study was performed. In total, 353 individuals were included after propensity score matching (PSM), with 136 in the day surgery group (DSG) and 217 in the inpatient surgery group (ISG). Results: The 24-hour discharge rate in the day surgery group (DSG) was 93.38% (127/136). Regarding postoperative complications (PPCs), no difference between the two groups was found (DSG vs. ISG: 11.76% vs. 11.52%, P=0.933). In the DSG, a shorter length of stay after surgery (LOS) (1.47±1.09 d vs. 2.72±1.28 d, P＜0.001) and reduced drainage time (8.45±3.35 h vs. 24.11±5.23 h, P＜0.001) were found, while the drainage volume per hour (mL/h) was not notably divergent between the relevant groups (P=0.312). No difference was observed in the cost of equipment and materials between the two groups (P=0.333). However, the average hospital cost and drug cost of the DSG were significantly lower than those of the ISG (P＜0.001). Conclusions: The study indicated that the implementation of VATDS showed no difference in PPCs but resulted in shorter in-hospital stays, shorter drainage times and lower hospital costs than inpatient surgery. These results indicate the safety and feasibility of VATDS for a group of highly selected patients with early-stage NSCLC.